(untitled) (Polis (Santiago), 2018)
In this article the author develops a generation and gender perspective to cultural consumption of middle class youngsters in Chile, through an unconventional approach to the night life entertainment in the context of post-dictatorship. The text explores the ways in which society relates to youth and new models of identity, making a counterpoint to the socialization that was generated in the previous cultural model to this age group. He thus focuses on two areas of entertainment characteristic of the youth, and in the codes of this generation. As one of the findings, the author highlights a transition from reference groups to consumer groups.